Exploring the possibility of an Ubuntu-based political philosophy - Furman, Katherine Elizabeth (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2013)
It is typically said that there are two questions that political philosophy seeks to address: 'who gets what?' and 'who decides on who gets what?' South Africa, along with much of the rest of the world, has answered the second question badly and currently ranks as one of the world's most unequal societies. Counter-intuitively, South Africa maintains a social-political order that (re)produces this inequality along with great enthusiasm for ubuntu, an African ethic that at a minimum requires that we treat each other humanely. However, due to the view that ubuntu has been co-opted in support of South Africa's unjust system, ubuntu has largely been ignored by radical thinkers. The aim of this thesis is therefore to explore the possibility of an ubuntu-based political philosophy, with the core assumption that political philosophy is rooted in ethical theory. Three tasks are therefore undertaken in this thesis. Firstly, ubuntu is articulated as an ethic. Secondly, it is compared to similar Western ethical theories in order to determine if there are distinguishing characteristics that make ubuntu a more appropriate founding ethic for South African political philosophy. Finally, whether ubuntu can find real-world applicability will be assessed by looking at the way ubuntu has been used in the law
Keywords: Ubuntu|Political philosophy|Ethical theories|Law|South Africa|Ubuntu (Philosophy) -- Research -- South Africa|Political science -- Philosophy -- Research|Philosophy, African -- Research|Social values -- Research -- South Africa|Ethics -- Research -- South Africa